Bupivacaine liposomal injectable suspension (Nocita®) provides postoperative analgesia following eyelid injection in dogs undergoing enucleation - Cullen, Megan Anne (Kansas State University, 2023)
OBJECTIVE: To evaluate the effectiveness of bupivacaine liposomal injectable suspension (BLIS) in reducing post-operative pain in dogs undergoing enucleation. ANIMALS: 30 dogs PROCEDURES: Client-owned dogs were randomly assigned to receive BLIS or saline. Dogs were premedicated with hydromorphone 0.1 mg/kg and acepromazine 0.01-0.04 mg/kg, induced with propofol to effect, and maintained with isoflurane. Dogs received a subconjunctival enucleation. Immediately prior to incision closure, the subcutaneous eyelid tissues were injected with BLIS or saline in a ring-block manner. All dogs received an oral 0.1 mg/kg dose of meloxicam at 8 hours postoperatively. Pain scoring and algometry of the incision was performed preoperatively and at 0, 1, 2, 4, 8, 24, 36, 48, and 72 hours postoperatively. Dogs received meloxicam following the 8-hour measurements. Rescue analgesia occurred with a pain score ≥3 in any category or ≥10 total. RESULTS: Fewer dogs in the BLIS group (p=0.010) required rescue analgesia (20% versus 66% of saline controls). Dogs receiving BLIS had higher algometry values at T0 (p=0.045) and lower algometry values at T24 (p=0.02) and T48 (p=0.014). Pain scores at T1 (p=0.042) were higher in dogs that received saline. In all dogs that did not require rescue analgesia (both BLIS and saline), there was a significant increase in algometry values between T8 and T24 (p=0.0056). CLINICAL RELEVANCE: Fewer dogs receiving BLIS required rescue analgesia, supporting its use as part of a multimodal pain management plan.
Keywords: Enucleation; Bupivacaine; Liposome; Dog; Pain